Change the culture, change the game the breakthrough strategy for energizing your organization and creating accountability for results - Connors, Roger (Tantor Media, 2011)
Roger Connors and Tom Smith show how leaders can achieve record-breaking results by quickly and effectively shaping their organizational culture to capitalize on their greatest asset, their people.
"Bonus material, multimode CD.". - Hard copy version record
Keywords: Organizational behavior; Corporate culture; Responsibility; Management; Comportement organisationnel; Culture d'entreprise; Responsabilité; Gestion; management; BUSINESS & ECONOMICS; Industrial Management; BUSINESS & ECONOMICS; Management; BUSINESS & ECONOMICS; Management Science; BUSINESS & ECONOMICS; Organizational Behavior; Downloadable audio books; Audiobooks; Livres audio